2022
DOI: 10.1055/a-1788-5802
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mode of Delivery on Maternal and Neonatal Outcomes during Periviable Birth (22–25 Weeks)

Abstract: Objective: To compare the maternal and neonatal complications of periviable birth by delivery route. Study Design: A retrospective cohort study of periviable deliveries (22w0d-25w6d) from 2013-2020 at a tertiary teaching institution was conducted. Deliveries were grouped by mode of delivery. Excluded deliveries included pregnancy termination, anomaly, or undesired neonatal resuscitation. The primary composite maternal outcome included death, intensive care admission, sepsis, surgical site infection, unplanned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…18 When limited to periviable infants, recent retrospective cohort studies found no association between MOD and severe IVH. 11,19 Our results suggest that, despite the MOD being associated with the physiology of IVH, the influence is not sufficiently strong to be associated with severe IVH.…”
Section: Discussionmentioning
confidence: 69%
“…18 When limited to periviable infants, recent retrospective cohort studies found no association between MOD and severe IVH. 11,19 Our results suggest that, despite the MOD being associated with the physiology of IVH, the influence is not sufficiently strong to be associated with severe IVH.…”
Section: Discussionmentioning
confidence: 69%
“…Obviously, the relationship between vaginal delivery and threshold ROP may be a link, although not necessarily a causal relationship [27] . During the natural delivery process, the mechanism of vaginal delivery and the stress dynamics may be harmful to the fetal cerebral blood vessels, leading to ischemia and subsequent reperfusion and/or oxidative stress, accompanied by related imbalance of hyperoxiahypoxia [28] . Both of the mechanisms can promote the release and formation of neoangiogenesis mediators induced by hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…No randomized controlled trial of cesarean delivery vs. vaginal delivery for periviable births has been conducted. A recent retrospective cohort study [16] of 274 periviable births in 230 mothers at 22–25 weeks gestational age by mode of delivery demonstrated no impact of route of delivery on neonatal survival or intact neonatal survival. Furthermore, head entrapment was rare during vaginal breech delivery.…”
Section: Cesarean Section For Fetal Indicationsmentioning
confidence: 99%